Strategic Vendor Partnership Model for Global E-Commerce Platforms Driving Category Growth and Enhanced Customer Experience - Geraldine Chika Nwokocha; Olakunle Babatunde Alao; Opeyemi Morenike Filani (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The growth of global e-commerce platforms depends significantly on strategic vendor partnerships that drive category expansion and enhance customer experience. This paper presents a conceptual framework for designing and managing vendor partnerships that align operational capabilities, market dynamics, and customer-centric strategies. Drawing from an extensive review of existing literature, including studies on e-commerce operations, vendor relationship management, and digital supply chain integration, the study proposes a multi-dimensional model for partnership evaluation, performance measurement, and strategic alignment. The framework emphasizes collaboration, trust-building, technology integration, and data-driven decision-making to optimize category growth, inventory efficiency, and customer satisfaction. The study provides both theoretical and managerial insights for e-commerce platform managers, strategic planners, and supply chain professionals, offering a standardized approach for leveraging vendor partnerships to achieve sustainable competitive advantage.